Training needs of librarians in 100 state colleges and universities in the Philippines - Recalde, Hipolita Rea 1948-
This study determined the training needs of the librarians in the 100 colleges and universities in the Philippines. It used a structured questionnaire to gather data from the 193 respondents selected through stratified sampling. These respondents represented 70 of the 100 SUCs in the country. The results showed that the SUCs librarians are mostly females; 42.63 years of age; graduates of baccalaureate degrees in different subject fields and continue to improve educationally by enrolling in courses leading to post graduate degrees; hold different position/titles; perform duties and responsibilities according to their job descriptions; possibly regularly promoted; licensed and unlicensed; members of national as well as regional/local library associations; and skilled in cataloguing and classification, acquisition of library materials and management and supervision. The results also showed that the SUCs librarians definitely need specialized and intensive training in emerging or new aspects of library work brought about by the introduction of new information technologies into the library systems; the SUCs librarians should also be trained in other traditional aspects of library work to reinforce and update what they already know. It was also discovered that some SUCs libraries lack staff as evidenced by the existence of "one-woman librarians". Training programs were proposed based on the perceived needs of the SUCs librarians.